Screening, Diagnosis, and Management of Patients With Alcohol Use Disorders at Bwindi Community Hospital, Uganda - Kuule, Yusufu; Dobson, Andrew E.; Harries, Anthony D.; Mutahunga, Birungi; Stewart, Alex G.; Wilkinson, Ewan (Frontiers in Public Health, 2018)
Introduction: The harmful use of alcohol is a growing global public health concern, with Sub-Saharan Africa at particular risk. A large proportion of adults in Uganda consume alcohol and the country has a high prevalence of alcohol use disorders (AUD), almost double that for the African region as a whole. Bwindi Community Hospital, in rural western Uganda, recently introduced a program of screening, diagnosis and management of AUD and we assessed how this worked. Methods: This was a cross-sectional study in three departments (out-patients, adult in-patients and sexual & reproductive health) of Bwindi Community Hospital assessing numbers of patients screened, diagnosed and treated with AUD between January 2014 and June 2017. Data sources included the hospital electronic data base and departmental case files. Frequencies and proportions are reported and odds ratios used to compare specific factors associated with medical interventions. Results: Altogether, 82,819 patients attended or were admitted to hospital, of whom 8,627 (10.4%) were screened and 273 (3.2%) diagnosed with AUD. The adult in-patient department recorded the largest number with AUD (n = 206) as well as a consistent increase in numbers in the last 18 months of the study. Of those with AUD, there were 230 (84%) males, 130 (48%) aged 36–60 years, and 131 (48%) with medical non-alcohol related diagnostic categories. Medical/supportive interventions included guidance and counselling to 168 (62%), community social support to 90 (33%), mental health service referrals for 75 (27%), detoxification for 60 (22%) and referral to Alcoholics Anonymous for 41 (15%). There were 36 (15%) patients who received no medical/supportive interventions, with significantly higher proportions in patients with surgical alcohol-related disease and pregnancy-related conditions (P < 0.05). Conclusion: Bwindi Community Hospital has implemented a program for AUD in three departments, with most individuals screened and managed in the adult in-patient department. While a variety of interventions were given to those with AUD, 15% received no intervention and this deficiency must be addressed. Program performance could improve through better screening processes, ensuring that 100% of those with AUD receive a medical/supportive intervention and raising public awareness.